Lecturers’ Perspectives on Difficult Biology Education Courses in Nigerian Colleges of Education - Edidiong Emmanuel AKPAN (Journal of General Education and Humanities, 2025)
The study examines lecturers’ perceptions of challenging courses in the Biology Education curriculum at colleges of Education in Southwest Nigeria. Using a descriptive survey method with 25 lecturers, data were collected through a validated questionnaire (r = 0.74). The results show that more female lecturers (57%) are compared to their male counterparts (43%). The findings also revealed that 14 lecturers held M.Ed./MSc (Ed), 6 had Ph.D., while 3 possessed B.Ed/BSc (Ed). The data further indicated that lecturers with 1 to 3 years and 4 to 6 years of experience were more numerous. The study identified 14 courses in the NCE Biology Education curriculum that lecturers found difficult. Courses such as Viruses, Bacteria, and Lower Plants (79.2%), Diversity of Chordates (78.2%), and Genetics (69.1%) were perceived as the most challenging. The research concludes that lecturers at the College of Education consider some courses they teach from NCE 1 to 3 as difficult. Recommendations include increased use of demonstrations to facilitate understanding of abstract concepts.